Physical Activity During Pregnancy and Its Impact on Postpartum Depression Risk: A Narrative Review - Czernic-Goławska, Klaudia; Falana, Joanna; Kozłowska, Jana; Orłowska, Maria; Kwiatkowska, Anna; Wielogórska, Aleksandra; Trojnar, Karolina; Przepióra, Agnieszka; Żmigrodzka, Anna; Sanocka, Maria; et al. (Quality in Sport, 2026)
Background. Pregnancy and the early postpartum period involve physiological and psychosocial changes that may increase vulnerability to depressive symptoms after childbirth. Safe and accessible preventive strategies, including physical activity, are therefore of growing interest. Aim. The aim of this narrative review was to summarize current evidence on the relationship between physical activity during pregnancy and the risk of postpartum depression. Material and methods. A structured search of PubMed, Scopus, and Google Scholar was conducted. Studies on pregnant women, prenatal physical activity, and postpartum depressive symptoms assessed with validated instruments, especially the Edinburgh Postnatal Depression Scale, were included. Results. Available evidence suggests that women who remain physically active during pregnancy tend to report fewer postpartum depressive symptoms. Better outcomes were most often observed with regular moderate-intensity exercise, programs lasting at least 12 weeks, and activity levels meeting current recommendations. Aerobic exercise, yoga, mind-body exercise, and relaxation-oriented interventions appear particularly promising. Conclusions. Prenatal physical activity may be an accessible and clinically relevant component of postpartum depression prevention. Further studies are needed to clarify the most effective dose, modality, and implementation strategy.